The Environment Effects of Fish Cages Farming in the Euphrates River at Mysayyib District on Water Quality at the Farms and at the Myssayyib Water Purification Stations-2013 - AL-Khaphaji, Raad M.; Mahdi, Khaleel M.; Hamed, Raghad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study aimed to investigate the effects of cages of fish farming of Mussayyib district,The fish farming have been selected at Euphrates river with in Mussayyib districtBabylon province the area of study extend 3 Km at the river and includes 541 cages in water with in 46 fish farming . Water samples were taken from 3 stations three times within one month for each two of them were taken from two water purification stations in mussayyib ,physical and chemical examination of water quality were taken ,The results for samples from the fish farming indicated that PH and salinity of water within acceptable levels, high proporation of dissolved oxygen and vital oxygen required were very high while the turbidity was more the permissible limits, the test and oder of water were not acceptable for the resuts for water samples of the water purifications stations which indicated that turbidity was high ,test and oder were not acceptable,pH within the acceptable level the TDS and chlorides were more than permissible limits while the polluted materials were more than acceptable levels.